2013
DOI: 10.3390/v5030777
|View full text |Cite
|
Sign up to set email alerts
|

Th17 Lymphocytes in Respiratory Syncytial Virus Infection

Abstract: Infection by respiratory syncytial virus (RSV) affects approximately 33 million infants annually worldwide and is a major cause of hospitalizations. Helper T lymphocytes (Th) play a central role in the immune response during such infections. However, Th lymphocytes that produce interleukin 17 (IL-17), known as Th17 lymphocytes, in addition to been protective can also cause pathology that accompany this type of infection. The protective effects of Th17 is associated with better prognosis in most infected indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
65
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(66 citation statements)
references
References 74 publications
0
65
0
1
Order By: Relevance
“…In contrast, IL-17 has no direct effect on airway hyper-responsiveness, which is solely Th2-mediated (50). In this context, a number of studies showed that RSVinfected mice simultaneously produced IL-17 and IL-13 suggesting that the Th17 response is concomitant with the Th2 response (50,55,56). Thirdly, IL-17 has been associated with increased neutrophilic infiltration in the lungs.…”
Section: Th17 Cells and Rsvmentioning
confidence: 99%
See 3 more Smart Citations
“…In contrast, IL-17 has no direct effect on airway hyper-responsiveness, which is solely Th2-mediated (50). In this context, a number of studies showed that RSVinfected mice simultaneously produced IL-17 and IL-13 suggesting that the Th17 response is concomitant with the Th2 response (50,55,56). Thirdly, IL-17 has been associated with increased neutrophilic infiltration in the lungs.…”
Section: Th17 Cells and Rsvmentioning
confidence: 99%
“…Firstly, IL-17 will cause exaggerated mucus production (50,55). Secondly, IL-17 is thought to enhance Th2 cytokine production in a Th2 skewed environment (50).…”
Section: Th17 Cells and Rsvmentioning
confidence: 99%
See 2 more Smart Citations
“…However, this may be an overly simplistic approach, as a recent study in mice has reported that shifting the host immune response toward T h 1 actually decreases the production of RSV-neutralizing antibodies, which would have the effect of limiting the effectiveness of a vaccine [90 • ]. In addition to T h 1 and T h 2 lymphocytes, the subpopulation of T h 17 lymphocytes has been implicated in RSV infection, further adding to the complexity of the host immune response [91].…”
Section: Progress Toward An Rsv Vaccine: Closer Than Evermentioning
confidence: 99%